Characterization of anxiolytic and neuropharmacological activities of Silexan - Kumar V. (My University, 2025)
Summary Silexan is an essential oil produced from Lavandula angustifolia flowers with proven clinical efficacy for the treatment of anxiety disorders. The present study was conducted to assess its anxiolytic activity and to screen for neuropharmacological properties in rats and mice of either sex. Silexan (3, 10, and 30 mg/ kg, intraperitoneally), lorazepam (5 mg/kg, p.o.), or diazepam (3 mg/kg, p.o.) were administered once daily for 7 consecutive days. Experiments were conducted 1 h after the last drug or vehicle administration. All the three doses of Silexan showed significant and dose-dependent anxiolytic activity in the used pharmacological models (open-field test, elevated plus-maze test, elevated zeromaze test, social interaction test, and novelty-induced suppressed feeding latency test), which was comparable to that of the standard anxiolytic agent lorazepam. In addition, Silexan amplified pentobarbital-induced sleeping time, but in contrast to diazepam was found to be devoid of any significant effect on locomotor activity and muscle-grip performance © Springer-Verlag Wien 2013.